2020
DOI: 10.1177/1024529420930323
|View full text |Cite
|
Sign up to set email alerts
|

Financialization and union decline in Canada: The influence on sectors and core industries

Abstract: This article explores the long-run relationship between financialization and union density in Canada’s non-financial sector. Drawing on critical political economy literatures, we argue that the shareholder business model, the growing use of financial assets and leading global industries have led to a restructuring of labour markets and unionized workforces. Evidence from panel data analysis suggests that the negative relationship between financialization and union density holds when controlling for ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In general, non-financial corporations can become financialised by either increasing their corporate debt ratios (either to fund share buy-backs or invest) or by becoming listed on the stock market and thus focused on maximising shareholder returns. The following two hypotheses are derived from this: Hypothesis 6: Increased corporate debt ratios will be negatively associated with union density Hypothesis 7: Increased exposure of non-financial corporations to stock markets will be negatively associated with union density A number of econometric studies have demonstrated that the growth of the so-called FIRE sector 4 (Finance, insurance, and real estate) relative to the real economy, employment in financial intermediation and the FIRE sector, as well as corporate debt, financial openness, and stock market price fluctuations are strongly associated with the decline of unionisation rates and union power in a wide range of advanced economies over the past five decades (Darcillon, 2015;Dupuis et al, 2020;Kollmeyer and Peters, 2019;Meyer, 2019;Mohamed and Darcillon, 2023;Peters, 2011). In a study that is more focused on financialisation in EU countries, Vachon et al (2016) show that financialisation measured in terms of employment in the FIRE sector has contributed to the reduction in union density in the EU since 1981, given that workers in finance and insurance are rarely unionised.…”
Section: Drivers Of Union Density: Key Hypotheses and Evidencementioning
confidence: 99%
“…In general, non-financial corporations can become financialised by either increasing their corporate debt ratios (either to fund share buy-backs or invest) or by becoming listed on the stock market and thus focused on maximising shareholder returns. The following two hypotheses are derived from this: Hypothesis 6: Increased corporate debt ratios will be negatively associated with union density Hypothesis 7: Increased exposure of non-financial corporations to stock markets will be negatively associated with union density A number of econometric studies have demonstrated that the growth of the so-called FIRE sector 4 (Finance, insurance, and real estate) relative to the real economy, employment in financial intermediation and the FIRE sector, as well as corporate debt, financial openness, and stock market price fluctuations are strongly associated with the decline of unionisation rates and union power in a wide range of advanced economies over the past five decades (Darcillon, 2015;Dupuis et al, 2020;Kollmeyer and Peters, 2019;Meyer, 2019;Mohamed and Darcillon, 2023;Peters, 2011). In a study that is more focused on financialisation in EU countries, Vachon et al (2016) show that financialisation measured in terms of employment in the FIRE sector has contributed to the reduction in union density in the EU since 1981, given that workers in finance and insurance are rarely unionised.…”
Section: Drivers Of Union Density: Key Hypotheses and Evidencementioning
confidence: 99%
“…Several empirical studies demonstrate that the financialisation of corporate governance has led to the breach of employment contracts, workforce downsizing, worsening workplace conditions and lower wages (Appelbaum et al, 2013; Darcillon, 2016). Further, more recent empirical work shows that financialised corporations also undermine labour's organisational capacity via two parallel processes (Dubuis et al, 2020; Kollmeyer & Peters, 2019; Peters, 2011). First, indebted firms tend to hire nonunionised employees to avoid union premia and reduce labour costs, generating incentives for other employees to not join or leave unions.…”
Section: Financialisation Household Indebtedness and Industrial Actionmentioning
confidence: 99%
“…This is particularly so where financial markets impose themselves in GPNs directly, by reshaping commodities as standardised tradable financial securities (Palpacuer, 2008;Newman, 2009;Purcell, 2018). The impersonal force of market-based financial mechanisms compresses time and standardises return and profit expectations (and their distributions to asset owners) in a way that greatly enhances the disciplining role of finance, resulting in downsizing, outsourcing, the increased use of precarious contracts and a decline in union density (Dupuis et al, 2020;Kollmeyer & Peters, 2019). Bowman (2018), for example, documents how shareholder pressures favoured downward wage pressure over productivity investments in the South African mining industry.…”
Section: The Interdependency Of Us Dollar Market-based Finance and Gl...mentioning
confidence: 99%